Inclusive Policy in Tribhuvan University: A Case of Its Pre and Post Implementation (Researcher: A Research Journal of Culture and Society, 2021)
Tribhuvan University (TU), a leading institution of higher education in Nepal covers 83 percent educational enrolment for higher-level education. It has been implementing inclusive policy since 2009 in order to mitigate inequality in composition of higher education governance. The main assumption of the policy action of inclusion is to increase the participation of excluded groups to maintain proportional equilibrium to privileged groups. Is the policy practice working as its assumption? This study has explored the answer of this question. The result shows that the increasing participation status of women, Indigenous Nationalities and Dalit. It has justified the relevancy of continuity of inclusive policy practice. However, the participation of two privileged groups i) Bahun and Chhetri and ii) Newar is not found remarkable decreased. To present the concluding result the article has contained about higher education governance and TU’s inclusive policy legal provision in introduction. After that, it has included the result, discussion and conclusion interpreting comparative data presentation of policy parget groups’ pre and post policy practice participation status.